2021
DOI: 10.3892/etm.2021.10555
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen gas post‑conditioning alleviates cognitive dysfunction and anxiety‑like behavior in a rat model of subarachnoid hemorrhage

Abstract: Subarachnoid hemorrhage (SAH) results in high rates of mortality and lasting disability. Hydrogen gas (H 2 ) is an antioxidant with demonstrated neuroprotective efficacy. The present study examined the therapeutic efficacy of H 2 inhalation on early brain injury following experimental SAH in rats and the potential underlying molecular mechanisms. The rats were randomly separated into three groups (n=36 per group): Sham, SAH and SAH + H 2 . Endovascular perforation of the right internal carotid artery was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Concerning the emotional disorders, some studies have shown the promising use of H 2 for treating the depressive-like behaviors provoked by mild chronic unpredictable stress [ 29 ] and the anxiety-like behaviors associated with morphine-withdrawal [ 34 ] or with a subarachnoid hemorrhage in rodents [ 35 ]. Despite that, the effects of H 2 on the emotional disorders accompanying neuropathic pain have not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the emotional disorders, some studies have shown the promising use of H 2 for treating the depressive-like behaviors provoked by mild chronic unpredictable stress [ 29 ] and the anxiety-like behaviors associated with morphine-withdrawal [ 34 ] or with a subarachnoid hemorrhage in rodents [ 35 ]. Despite that, the effects of H 2 on the emotional disorders accompanying neuropathic pain have not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…This is also seen in the clinical literature, in which patients tend to have worsening depression in the initial 12 months following SAH [54]. In preclinical models of SAH, damages to the ventromedial prefrontal cortex, perirhinal cortex, and hypothalamus were associated with the development of anxiety [44,55]. While no studies have directly investigated the anatomic correlates of post-SAH depression, patients with SAH have shown altered functional connectivity in the cingulate cortex, which is also seen in major depressive disorder [56,57].…”
Section: Discussionmentioning
confidence: 74%
“…The percentage of open arm entry for the EM demonstrated a moderate (> 70%) correlation with and accuracy for predicting damage to the amygdala. While anxiety-like behavior has been frequently reported in experimental models of SAH, no preclinical studies have directly linked SAH-related anxiety to cellular damage in the amygdala [51][52][53].…”
Section: Discussionmentioning
confidence: 99%